Relações trigonométricas fundamentais - Bezerra, Antônio Almir (2014)
BEZERRA, Antônio Almir. Relações trigonométricas fundamentais. 2014. 59 f. Dissertação (Mestrado em Matemática em Rede Nacional) - Centro de Ciências, Universidade Federal do Ceará, Fortaleza, 2014. === Submitted by Erivan Almeida (eneiro@bol.com.br) on 2014-08-18T18:26:02Z No. of bitstreams: 1 Dissertacao de Antonio Almir Bezerra.pdf: 1732043 bytes, checksum: 6d0f5917cd52b68f851df7a78b900192 (MD5) === Approved for entry into archive by Rocilda Sales(rocilda@ufc.br) on 2014-08-19T15:35:37Z (GMT) No. of bitstreams: 1 Dissertacao de Antonio Almir Bezerra.pdf: 1732043 bytes, checksum: 6d0f5917cd52b68f851df7a78b900192 (MD5) === Made available in DSpace on 2014-08-19T15:35:37Z (GMT). No. of bitstreams: 1 Dissertacao de Antonio Almir Bezerra.pdf: 1732043 bytes, checksum: 6d0f5917cd52b68f851df7a78b900192 (MD5) Previous issue date: 2014 === The present research aims to present classic demonstrations of the fundamental relations of Trigonometry,with a simple approach, and exploring flat shapes. The intention is to make such demonstrations better known and provide a highlight for Trigonometry, since they are essential in solving problems of everyday life. For this purpose, we made a historical highlighting of the importance of trigonometry in the mathematical context. Since we know Trigonometry is loosing its status and not being considered essential in basic education anymore, such demonstrations, associated with the flat shapes, may be used as a model class. Therefore, we highlight the following fundamental relations: Basic Trigonometric relations, Derived Relations, Sine of the Sum and Difference of Two Arcs, Cosine of the Sum and Difference of Two Arcs, Double Arcs, Half Arc, Transformation in Product and Applications. For the demonstration ot these relations we used some area results, cosine law, Ptolemy’s theorem and the theorem of the broken chord Plane Geometry. We believe that Trigonometry is linked to the formation of these flat shapes. Thus, such demonstrationas associated to these flat shapes may serve to improve the Trigonometry teaching- learning and as motivator for students and teachers seeking to enhance their knowledge in mathematics. === Neste trabalho apresentamos algumas relações trigonométricas fundamentais e suas demonstrações. Tais relações merecem destaque, pois são essenciais na resolução de problemas nas diversas áreas do conhecimento. Inicialmente fizemos um breve histórico da Trigonometria destacando a sua importância no contexto da Matemática. Em sequência apresentamos as relações fundamentais, dentre elas, enfatizamos as fórmulas da adição de arcos, cujas demonstrações utilizamos área de figuras planas, a lei dos cossenos e a lei dos senos. Além disso, mostramos como estas fórmulas se relacionam com o Teorema da Corda Quebrada e o Teorema de Ptolomeu da Geometria Plana. Explorando a relações entre Trigonometria e Geometria Plana. Procuramos mostrar a importância desta teoria no ensino médio motivando alunos e professores a buscar um maior interesse pelo conhecimento em Matemática.